Pengaruh Literasi Keuangan, Inklusi Keuangan, Akses Permodalan, dan Penggunaan E-commerce Terhadap Kinerja UMKM (Studi Pada Pelaku UMKM di Kabupaten Blitar) - Reza, Oktayuan Nanda; Mawardi, M. Cholid; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2024)
This research explores the impact of financial literacy, financial inclusion, access to capital, and the use of e-commerce on UMKM performance in Blitar Regency. The study utilized a quantitative approach, gathering information through a questionnaire that employed a Likert scale for responses. The sample for this study consisted of 100 MSMEs from Blitar Regency, all of which were registered with the Blitar Regency Cooperatives and SME Office. The data underwent analysis using the SPSS software, specifically version 25. The findings indicate that financial literacy, financial inclusion, access to capital, and the use of e-commerce collectively exert a significant influence on UMKM performance. Notably, each of these factors—financial literacy, financial inclusion, access to capital, and the use of e-commerce—contributes positively and markedly to the improvement of UMKM performance.Keywords: UMKM performance, financial literacy, financial inclusion, access to capital, use of e-commerce